Biological sampling in the deep sea - Clark, Malcolm R. , 1956-; Consalvey, Mireille; Rowden, A. A. [ (Ashley Alun)] (Wiley-Blackwell, 2016)
"The major part of this excellent new book covers all the major types of gear, each in a separate chapter. Chapters each follow a standard format and include a range of carefully-selected illustrations"